Scadding revisited: a proposed staging system for sardiac sarcoidosis - Berman, Jeffrey S; Govender, Praven; Ruberg, Frederick L.; Mazzini, Michael; Miller, Edward J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Not available